Estimating software costs : bringing realism to estimating - Jones, Capers (McGraw-Hill Companies, 2007)
"Deliver software projects on time and within budget. This fully updated and expanded volume provides cost-estimating methods for projects using modern technologies including Java, object-oriented methods, and reusable components. Written by a pioneer and leading authority in the field of software estimation, this new edition is the definitive resource for developers building complex software."